Determination of nutrients and metals content in liquid generated from composted food waste - Muda, Nur Hanismahiza (2015)
The increasing amount of food waste put more pressure on already municipal solid waste management systems especially in cities due to increasing of population growth and their eating habits. Composting has been recommended in order to manage waste especially for the disposal of food waste. Composting food waste is beneficial as soil amendment. This study is conducted to evaluate the nutrients (NH3-N-, NO3 - and PO4 3-) and metals (Fe2+, Mn2+ and Zn2+) content in liquid generated from composted food waste (fruits waste and vegetables waste). The nutrients and metals were analyzed based on the composition of bacterium and molasses. The chemical analysis of sample was carried out by using Hach spectrophometer DR6000. The ratio of fruits waste or vegetables waste, molasses and bacterium are 1kg for fruits waste or vegetables waste, 0.5 – 3kg of molasses with 50 – 500mL bacterium. The duration of composting is eighteen weeks. The concentrations of NH3-N, NO3 - and PO4 3- for composted fruits waste and vegetables waste are 200 – 1700mg/L while the metals concentrations are low which below than 30mg/L. The best ratio of composting food waste which consist of mixed fruits and vegetables waste, bacterium and molasses is 1:500:0.5 (kg:mL:kg). The result showed that the composted both fruits and vegetables wastes are potentially to be used as fertilizer for agriculture use because of high nutrient content.